Sedimentary facies analysis and depositional model of gravity-flow deposits of the Yanchang Formation, southwestern Ordos Basin, NW China. Issue 7 (2nd October 2016) - Liu, F.; Zhu, X.; Li, Y.; Xue, M.; Sun, J.
ABSTRACT: During the deposition of the Chang-7 (Ch-7) and Chang-6 (Ch-6) units in the Upper Triassic, gravity flows were developed widely in a deep lake in the southwestern Ordos Basin, China. Based on cores, outcrops, well-logs and well-testing data, this paper documents the sedimentary characteristics of the gravity-flow deposits and constructs a depositional model. Gravity-flow deposits in the study area comprise seven lithofacies types, which are categorised into four groups: slides and slumps, debris-flow-dominated lithofacies, turbidity-current-dominated lithofacies, and deep-water mudstone-dominated lithofacies. The seven lithofacies form two sedimentary entities: sub-lacustrine fan and the slump olistolith, made up of three and two lithofacies associations, respectively. Lithofacies association 1 is a channel–levee complex with fining-/thinning-upward sequences whose main part is characterised by sandy debris flow-dominated, thick-bedded massive sandstones. Lithofacies association 2 represents distributary channelised lobes of sub-lacustrine fans, which can be further subdivided into distributary channel, channel lateral margin and inter-channel. Lithofacies association 3 is marked by non-channelised lobes of sub-lacustrine fans, including sheet-like turbidites and deep-lake mudstones. Lithofacies association 4 is represented by proximal lobes of slump olistolith, consisting of slides and slumps. Lithofacies association 5 is marked by distal lobes of slump olistolith, comprising tongue-shaped debris flow lobes and turbidite lobes. It is characterised by sandy debris flow, muddy debris flow-dominated sandstone and sandstone with classic Bouma sequences. Several factors caused the generation of gravity flows in the Ordos Basin, including sediment supply, terrain slope and external triggers, such as volcanisms, earthquakes and seasonal floods. The sediment supply of sub-lacustrine fan was most likely from seasonal floods with a high net-to-gross and incised channels. Triggered by volcanisms and earthquakes, the slump olistolith is deposited by the slumping and secondary transport of unconsolidated sediments in the delta front or prodelta with a low net-to-gross and no incised channels.